DESCRIPTION OF NURSING INTERNSHIP STUDENT'S ANXIETY DURING THE PANDEMIC ERA - Amellia Mardhika; Selvyana Dewi Anggraeni; Anestasia Pangestu Mei Tyas; Lailatul Fadliyah; Emuliana Sulpat (Universitas Airlangga, 2023)
Introduction: COVID-19 changed students' educational activities, especially during internships taking into account the condition of the number exposed to COVID-19. A preliminary study conducted on 11 students showed that they all felt anxious about undertaking an internship during the pandemic. This can negatively impact quality of life, learning, academic performance, and clinical practice performance. The aim of this study is to find out the description of students' anxiety during internships. Methods: This research is a quantitative observational study with a descriptive research design”a sample of 148 students with a purposive sampling method. The variable in this study was detained students who were undergoing internships during the start of the COVID-19 pandemic. The instrument used in this study was the Hamilton Anxiety Rating for Scale (HAM-A), which had been tested for validity and reliability to see the level of student anxiety during the internship. The results of the questionnaire were then analyzed through descriptive/univariate analysis. Results: Almost all respondents had a mild anxiety level, 120 respondents (81.08%). Conclusions: A suitable coping mechanism for students during internships, is a strategy to deal with anxiety. Clarifying information, consistently implementing health protocols correctly, maintaining health by exercising regularly, eating healthy food, and communicating well with family and friends must still be carried out by students so that the support system remains stable